Comparison of dynamic response of three TLIF techniques on the fused and adjacent segments under vibration. Issue 3 (17th February 2021) - Wang, Qing-Dong; Guo, Li-Xin
Abstract: To explore which TLIF techniques are advantageous in reducing the risk of complications and conducive to bone fusion under the vibration. The L1–L5 finite element lumbar model was modified to simulate three different TLIF techniques (a unilateral standard cage, a crescent-shaped cage, and bilateral standard cages). The results showed that the crescent-shaped cage may reduce the risk of subsidence and provide a more stable and suitable environment for vertebral cell growth under the vibration compared to the other TLIF techniques. Unilateral cage may increase the risk of adjacent segment disease and cage failure including fatigue failure under vibration.